SOME INSTRUMENTS USED TO ACHIEVE ENVIRONMENTAL PERFORMANCE IN TOURIST ACCOMMODATION UNITS - Stefanica, Mirela (Studies and Scientific Researches. Economics Edition, 2018)
The paper highlights some instruments that help us to achieve environmental performance in tourist accommodation structures. The most known instruments used to achieve environmental performance are as follows: ISO 14001 standards (Environmental Management Standard), EMAS (European Eco-Management and Audit Scheme), and EU ECOLABEL. With the help of these instruments, we can identify and quantify the material and power resources consumed, the emissions and waste generated, we can evaluate their potential impact over the environment, and we can identify the options to reduce these impacts. The reasons at the basis of the creation of these instruments are extremely complex, going beyond the purely economic frame in order to enter an ethical sphere of debates inciting the spirit of almost all the population on the Globe, which is the type of planet that we leave as inheritance to our followers, the future generations. According to the reports of the European Commission regarding these instruments we have shown the evolution and the present situation of EMAS registrations and EU Ecolabel for European tourist accommodation services.